2019
DOI: 10.4186/ej.2019.23.5.107
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Bottom Ashes with Different Water Retainabilities on Properties of Expansive Mortars and Expansive Concretes

Abstract: This study investigates the influence of bottom ashes with different water retainabilities as an internal curing material on the performances of mixtures containing an expansive additive and fly ash. Two series of experiments were conducted: mortar containing expansive agent (expansive mortar) with a controlled w/b ratio and concrete containing expansive agent (expansive concrete) with a controlled initial slump. Test results indicate that workability of expansive mortar is improved due to retained water of bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 18 publications
(25 reference statements)
1
2
0
Order By: Relevance
“…[19][20][21]33 It was observed that the HSA mortars with 0 vol% HSA exhibited the greatest compressive strength while the compressive strength of the mortars trended to decrease with increasing HSA content. This finding is similar to Torkittikul 24 and Nguyen 22 that the compressive strength of the mortars containing BA as fine aggregate were lower than that of the plain mortar because of their total porosity with the replacement of dense aggregate with porous materials. Moreover, the results showed that the mortars with additional HSA of 30 to 50 vol% were found to slightly decrease in compressive strength when compared to the 20 vol% HSA mortars.…”
Section: Compressive Strengthsupporting
confidence: 87%
See 1 more Smart Citation
“…[19][20][21]33 It was observed that the HSA mortars with 0 vol% HSA exhibited the greatest compressive strength while the compressive strength of the mortars trended to decrease with increasing HSA content. This finding is similar to Torkittikul 24 and Nguyen 22 that the compressive strength of the mortars containing BA as fine aggregate were lower than that of the plain mortar because of their total porosity with the replacement of dense aggregate with porous materials. Moreover, the results showed that the mortars with additional HSA of 30 to 50 vol% were found to slightly decrease in compressive strength when compared to the 20 vol% HSA mortars.…”
Section: Compressive Strengthsupporting
confidence: 87%
“…Moreover, the utilization of industrial by-products as an additive to mortar and concrete as a supplementary cementitious material 20,21 leads to an overall decrease in the amount of cement used. Conventional BA is porous, granular, and is larger than cement particles, making it suitable for use as fine/coarse aggregates in mortars, concretes, 22 or lightweight concrete [23][24][25] for improving the thermal insulation properties 24 and/or for TES. 26 From previous works, substituting sand with the industrial waste materials (BA) incorporated with paraffin as a fine aggregate into building materials, as a heat storage aggregate (HSA) has not been previously undertaken.…”
mentioning
confidence: 99%
“…LWA can be in the form of coarse and fine aggregate and the more common aggregates used as a curing agent in self-curing concrete, which are natural-based, are expanded shale [75,76], expanded clay (LECA), [38,42,65,70,[77][78][79][80] and pumice [68,81,82]. Whereas the curing agent from by-product materials, often studied by researchers, is bottom ash [4,69,70,[83][84][85][86].…”
Section: Artificial Lightweight Aggregate (Lwa)mentioning
confidence: 99%